Anti-Tat Immunity in HIV-1 Infection: Effects of Naturally Occurring and Vaccine-Induced Antibodies Against Tat on the Course of the Disease - Cafaro, Aurelio (Vaccines (Basel), 2019)
HIV-1 Tat is an essential protein in the virus life cycle, which is required for virus gene expression and replication. Most Tat that is produced during infection is released extracellularly and it plays a key role in HIV pathogenesis, including residual disease upon combination antiretroviral therapy (cART). Here, we review epidemiological and experimental evidence showing that antibodies against HIV-1 Tat, infrequently occurring in natural infection, play a protective role against disease progression, and that vaccine targeting Tat can intensify cART. In fact, Tat vaccination of subjects on suppressive cART in Italy and South Africa promoted immune restoration, including CD4+ T-cell increase in low immunological responders, and a reduction of proviral DNA even after six years of cART, when both CD4+ T-cell gain and DNA decay have reached a plateau. Of note, DNA decay was predicted by the neutralization of Tat-mediated entry of Env into dendritic cells by anti-Tat antibodies, which were cross-clade binding and neutralizing. Anti-Tat cellular immunity also contributed to the DNA decay. Based on these data, we propose the Tat therapeutic vaccine as a pathogenesis-driven intervention that effectively intensifies cART and it may lead to a functional cure, providing new perspectives and opportunities also for prevention and virus eradication strategies.